Desa Tuksongo Borobudur Sebagai Bentuk Pengembangan Wisata Yang Berkelanjutan - Nuzulul Faidatun,; Rudi Susanto,; Aldi Wisnumurti, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The method of data analysis of this research is a qualitative descriptive analysis in the form of an in-depth description related to the application of sustainable tourism and sustainable tourism development strategies at the Economic Center of Tuksongo Village Borobudur. The results of the study explained that the implementation of sustainable tourism through the Village Economic Center program in Tuksongo Village, Borobudur District, Magelang Regency was considered not optimal, namely in the aspect of assistance assistance and aspects of institutional strengthening. Meanwhile, in the aspect of capital assistance, infrastructure assistance and partnership strengthening seem to have run well and are suitable to support community empowerment through the village economic hall program. The strategy carried out briefly includes providing financial assistance for the development of tourism villages issued by Balkodes Tuksongo, continuous tra ng, socializing the importance of good service to tourists, establishing souvenir stalls that will fully belong to the local community and also holding promotions introducing the diversity of tourist attractions in Tuksongo Village.